Early neurological injury after cardiac surgery: insights from a single centre prospective study - Nicolini, Francesco; Maestri, Francesco; Fragnito, Claudio; Belli, Loredana; Malchiodi, Laura; Venazzi, Antonella; Agostinelli, Andrea; Gallingani, Alan; De Carlo, Luigina; Gherli, Tiziano (Acta Biomedica Atenei Parmensis, 2013)
Background and aim of the work: The aim of this study was to report the incidence of early neurological complications after heart surgery, to identify preoperative and procedural risk factors for these complications and to assess their influence on postoperative outcome. Methods: Data were prospectively collected from 954 procedures: 520 coronary artery bypass grafting (CABG), 233 valve surgery, 100 combined CABG and valve surgery, 88 major aortic surgery, and 13 other procedures. Independent risk factors were analyzed by multivariate stepwise logistic regression model. Results: Early cerebral complications occurred in 94 patients (9.85%). Eleven patients (11.7%) had permanent cerebral symptoms and 83 (88.3%) had transient neurological symptoms only. Risk factors for early neurological complications were older age, chronic obstructive pulmonary disease, open cardiac chambers procedures, higher end-cardiopulmonary bypass lactate levels, blood transfusion, and the use of insulin in ICU. Conclusion: The results of this study suggest a relationship between metabolic and technical aspects of cardiopulmonary bypass management and early occurrence of neurological injury. Preoperative screening and intraoperative measures that ensure adequate cerebral perfusion, minimize embolization and improve systemic inflammatory response and hemodynamic performance appear mandatory in these patients. Future efforts will be necessary to strongly validate surrogate markers of early neurologic damage to predict neuropsychological dysfunction after cardiac surgery.